ХООСОН ЧАНАР БА МӨНХ ТЭНГЭР - О.Лхагва (Acta Mongolica, 2013)
Now Besso (his old friend) has departed from this strange world a little ahead of me. That means nothing. People like us…know that the distinction between past, present, and future is only a stubbornly persistent illusion. Immortality doesn’t mean a perpetual existence in time without end, but rather resides outside of time altogether. A. Einstein In the light of quantum physics and synergy conceptions the problem of interrelation between the emptiness - the one of Buddhists key teachings and Munkh Tengery- proper science of Nomads is firstly considered. Chinggis Khaan had often declared that his Great Empire has been created under the might of Munkh Tengery. To follow khaans revelation then all Great Steppe Empires of Huns, Turky and Mongolian may well be founded on the same ground of Tengery power. In this sence Tengery Power has stand for astonishing spiritual force promoting the mysterious civilizations of nomads in Great Steppe. It allows to suppose that undeniable fostering of Steppe Empires has a sacred origin.